Environmental exposures related to parental habits in the perinatal period and the risk of Wilms' tumor in children. (June 2020) - Rios, Paula; Bauer, Hélène; Schleiermacher, Gudrun; Pasqualini, Claudia; Boulanger, Cécile; Thebaud, Estelle; Gandemer, Virginie; Pellier, Isabelle; Verschuur, Arnauld; Sudour-Bonnange, Hélène; Coulomb-l'Hermine, Aurore; Spiegel, Alexandra; et al.
Highlights: Perinatal exposures due to maternal habits like smoking, alcohol consumption and domestic use of pesticides are suspected risk factors of Wilms' tumor. Our population-based case control-study shows that household insecticide use during pregnancy may be associated to an increased risk of Wilms' tumor. The study does not suggest any role of parental smoking or maternal drinking in the etiology of Wilms' tumor. Abstract: Introduction: Wilms' tumor is the most frequently diagnosed renal tumor in children. Little is known about its etiology. The aim of this study was to investigate the potential role of specific exposures related to parental habits such as parental smoking, maternal alcohol consumption and the use of household pesticides during pregnancy. Methods: The ESTELLE study was a nationwide case-control study that included 117 Wilms' tumor cases and 1100 control children from the general French population, frequency-matched by age and gender. Unconditional logistic regression was used to estimate odds ratios and 95 % confidence intervals. Results: After controlling for matching variables and potential confounders, the maternal use of any type of pesticide during pregnancy was associated with the risk of Wilms' tumor in children (OR 1.6 [95 % CI 1.1–2.3]). Insecticides were the most commonly reported type of pesticide and there was a positive association with their use (OR 1.7 [95 % CI 1.1–2.6]. The association was stronger when they were used more often than once a month (OR 1.9 [95 % CI 1.2–3.0]. Neither maternal smoking during pregnancy nor paternal smoking during preconception/pregnancy was associated with a risk of Wilms' tumor (ORs 1.1[95 % CI 0.7–1.8] and 1.1 [95 % CI 0.7–1.7], respectively). No association was observed with maternal alcohol intake during pregnancy (OR 1.2 [95 % CI 0.8–2.0]). Conclusion: Our findings suggest an association between the maternal use of household pesticides during pregnancy and the risk of Wilms' tumor.